Cholesterol modulates the rate and mechanism of acetylcholine receptor internalization - Borroni, Maria Virginia (2011)
Stability of the nicotinic acetylcholine receptor (AChR) at the cell surface is key to the correct functioning of the cholinergic synapse. Cholesterol (Chol) is necessary for homeostasis of AChRlevels at the plasmalemma and for ion translocation. Here we characterize the endocytic pathway followed by muscle-type AChR in Chol-depleted cells (Chol-). Under such conditions, the AChR is internalized by a ligand-, clathrin-, and dynamin-independent mechanism. Expression of a dominant negative form of the small GTPase Rac1, Rac1N17, abolishes receptor endocytosis. Unlike the endocytic pathway in controlCHOcells (1), accelerated AChR internalization proceeds even upon disruption of the actin cytoskeleton. Under Chol- conditions, AChR internalization is furthermore found to require the activity of Arf6 and its effectors Rac1 and phospholipase D. The Arf6-dependent mechanism may constitute the default endocytic pathway followed by the AChR in the absence of external ligands, membrane Chol levels acting as a key homeostatic regulator of cell surface receptor levels.